Synthesis and characterization of Bis (benzyltriphenylphosphonium) tetrachloromanganate (II) by using a Single crystal X-ray (College of Basic Education Research Journal, 2026)
Bis(benzyltriphenylphosphonium) tetrachloromanganate (II), a novel manganese(II) complex, was effectively synthesized and described in this work. Manganese (II) chloride and benzyltriphenylphosphonium chloride were directly reacted in a suitable solvent under carefully monitored conditions to create the complex. FT-IR, UV-Vis, and elemental analysis were among the spectroscopic and analytical methods used to examine the resultant crystalline compound. These methods confirmed that the Mn(II) center was coordinated with four chloride ligands in a tetrahedral geometry.
Keywords: triphenylphosphonium; ionic liquids; metal complex salts